GIS-based morphometric analysis of Kabani River in Kerala, India, using toposheet and CartoSat DEM - Sanjayan, M.S.; Brijesh, V.K. (Journal of Degraded and Mining Lands Management, 2026)
Morphometric analysis of Kabani River Basin in Wayanad district of Kerala was done using two different approaches. The first approach utilized CartoSat DEM with 30m resolution, and second used Survey of India (SOI) topographic maps of 1:50,000 scale. Drainage networks were digitally extracted from SOI toposheet using ArcGIS software. Drainage networks were created from the DEM (Digital Elevation Model) by using Hydrology tool available in ArcGIS. A comparative study of morphometric parameters derived by the two approaches revealed important insights into the advantages and limitations of each dataset for various applications. In the present study, it could be seen that drainage delineation done with CartoSat DEM data matched well with the ground truth than the drainage extracted from toposheets. The linear, areal and relief parameters derived from both the datasets are discussed in detail to show their significance in geomorphological and hydrogeological studies of the terrain.